Third Mission Accelerator Labs (TMALs): An exploratory study on the strategic evolution of sustainability in university-business incubators (UBIs) - Hassanein, Abdalla (AUC Knowledge Fountain, 2024)
Globally, higher education institutions (HEIs) are devoting rising resources in order to remain competitive, impactful and attractive within the ever-changing socio-economic developments and to well position and communicate their value among their stakeholders (Lafuente-Ruiz-de-Sabando, et al. 2018). Students today want to do more than just get a degree; they want to create businesses, develop new markets, and start social movements (Kay et al., 2010). Under the open innovation model, universities' third mission (TM) includes deeper linkages and engagements with the private and public sectors, emphasizing the development of entrepreneurial mindsets, skills, and incubation services to encourage new business ventures, in addition to teaching (their first and conventional mission) and researching (their second mission). The earliest known model of the TM is the idea of an entrepreneurial university. University Business Incubators (UBIs) have gained prominence in this entrepreneurial paradigm shift, providing support to early-stage founders and start-ups, fostering innovation, and transferring intellectual knowledge to practical applications for the broader community (Stal et al., 2016). However, concerns arise regarding environmental sustainability and growing socio-economic inequalities. Higher education must play a vital role in igniting attitudes, behaviors, and leadership for sustainable transformation. UBIs must evolve from their traditional focus on commercial entrepreneurship to promote and advance sustainable entrepreneurship knowledge and practices (Moreno et al., 2019). This research explores UBIs' strategic evolution to promote sustainable business innovation. It develops a model to ignite entrepreneurial attitudes and sustainability practices within different entrepreneurship education models to serve as empowering spaces for community-led sustainable growth and development.